Effects of Stomach Inflation on Cardiopulmonary Function and Survival During Hemorrhagic Shock: A Randomized, Controlled, Porcine Study. Issue 1 (July 2016) - Braun, Patrick; Putzer, Gabriel; Strapazzon, Giacomo; Wimmer, Angela; Schnell, Hermann; Arnold, Henrik; Neururer, Sabrina; Brugger, Hermann; Wenzel, Volker; Paal, Peter
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Ventilation of an unprotected airway may result in stomach inflation. The purpose of this study was to evaluate the effect of clinically realistic stomach inflation on cardiopulmonary function during hemorrhagic shock in a porcine model. Methods: Pigs were randomized to a sham control group (n = 9), hemorrhagic shock (35 mL kg −1 over 15 min [n = 9]), and hemorrhagic shock combined with stomach inflation (35 mL kg −1 over 15 min and 5 L stomach inflation [n = 10]). Results: When compared with the control group, hemorrhagic shock (n = 9) increased heart rate (103 ± 11 vs. 146 ± 37 beats min −1 ; P = 0.002) and lactate (1.4 ± 0.5 vs. 4.0 ± 1.9 mmol L −1 ; P < 0.001), and decreased mean arterial blood pressure (81.3 ± 12.8 vs. 35.4 ± 8.1 mmHg; P < 0.001) and stroke-volume index (38.1 ± 6.4 vs. 13.6 ± 4.8 mL min −1 m −2 ; P < 0.001). Hemorrhagic shock combined with stomach inflation (n = 10) versus hemorrhagic shock only (n = 9) increased intra-abdominal pressure (27.0 ± 9.3 vs. 1.1 ± 1.0 mmHg; P < 0.001), and decreased stroke-volume index (9.9 ± 6.0 vs. 20.8 ± 8.5 mL min −1 m −2 ; P = 0.007), and dynamic respiratory system compliance (10.8 ± 4.5 vs. 38.1 ± 6.1 mL cmH2 O −1 ; P < 0.001). Before versus after stomach evacuation during hemorrhagic shock, intra-abdominal pressure decreased (27.0 ± 9.3 vs. 9.8 ± 5.4 mmHg; P = 0.042). Survival in the sham control and hemorrhagic shock group was 9 of 9, respectively, and 3 of 10 after hemorrhagic shock and stomach inflation ( P < 0.001). Conclusions: During hemorrhagic shock stomach inflation caused an abdominal compartment syndrome and thereby impaired cardiopulmonary function and aerobic metabolism, and increased mortality. Subsequent stomach evacuation partly reversed adverse stomach-inflation triggered effects.